Dosimetric impact of intrafraction prostate rotation and accuracy of gating, multi-leaf collimator tracking and couch tracking to manage rotation: An end-to-end validation using volumetric film measurements. (March 2021) - De Roover, Robin; Hansen, Rune; Crijns, Wouter; Muurholm, Casper Gammelmark; Poels, Kenneth; Skouboe, Simon; Haustermans, Karin; Poulsen, Per Rugaard; Depuydt, Tom
Highlights: Intrafraction prostate rotations reduces target coverage and increases OAR dose. Gating, MLC tracking and couch tracking improves the dosimetric accuracy. Residual motion-related dose errors remain due to the lack of rotation correction. Abstract: Background and purpose: Both gating and tracking can mitigate the deteriorating dosimetric impact of intrafraction translation during prostate stereotactic body radiotherapy (SBRT). However, their ability to manage intrafraction rotation has not yet been thoroughly investigated. The dosimetric accuracy of gating, MLC tracking and couch tracking to manage intrafraction prostate rotation was investigated. Materials and methods: Treatment plans for end-to-end tests of prostate SBRT with focal boosting were generated for a dynamic anthropomorphic pelvis phantom. The phantom applied internal lateral rotation (up to 25°) and coupled vertical and longitudinal translation of a radiochromic film stack that was used for dose measurements. Dose was delivered for each plan while the phantom applied motion according to three typical prostate motion traces without compensation (i), with gating (ii), with MLC tracking (iii) or with couch tracking (iv). Measured doses for the four motion compensation strategies were compared with the planned dose in terms of γ-index analysis, target coverage and organs at risk (OAR) sparing. Results: Intrafraction rotation reduced the 3%(global)/2mm γ-index passing rate (γPR) for the prostate target volume by median (range) –33.2% (−68.6%, −4.1%) when no motion compensation was applied. The use of motion compensation improved the γPR by 13.2% (−0.4%, 32.9%) for gating, by 6.0% (−0.8%, 27.7%) for MLC tracking and by 11.1% (1.2%, 22.9%) for couch tracking. The three compensation techniques improved the target coverage in most cases. Gating showed better OAR sparing than MLC tracking or couch tracking. Conclusions: Compensation of intrafraction prostate rotation with gating, MLC tracking and couch tracking was investigated experimentally for the first time. All three techniques improved the dosimetric accuracy, but residual motion-related dose errors remained due to the lack of rotation correction.